2020
DOI: 10.1002/adtp.201900185
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Immune Cells with Trimannosylated Liposomes

Abstract: Dendritic cells (DCs) are a compelling target in cancer immunotherapy as they initialize strong antigen‐specific immune responses. Drug delivery systems (DDSs) such as liposomes provide the opportunity to deliver antigens and immunostimulatory molecules to DCs, which in turn initiate an antigen‐specific immune response. To address predominantly DCs, DDSs need to be equipped with targeting moieties. This study evaluates liposomes, bearing the oligosaccharide trimannose on their surface, for their ability to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…An alkyne-group enables the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) with functional groups, e.g., dyes like atto 488 azide or other azide-bearing molecules [ 25 ]. This reaction is known from literature and was adapted for the synthesized amphiphilic polyethers [ 31 , 32 ]. For this purpose, the terminal hydroxyl group of PEG was deprotonated using sodium hydride (NaH) (see supplement scheme S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…An alkyne-group enables the copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) with functional groups, e.g., dyes like atto 488 azide or other azide-bearing molecules [ 25 ]. This reaction is known from literature and was adapted for the synthesized amphiphilic polyethers [ 31 , 32 ]. For this purpose, the terminal hydroxyl group of PEG was deprotonated using sodium hydride (NaH) (see supplement scheme S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The latter is currently considered to be more effective in terms of cheap recombinant production and precise chemical modification compared to full antibodies or antibody-drug conjugates. More recently, also peptide-based targeting strategies [111,112] or multivalent mannose derivatives [113] have been exploited to guide nanoparticle delivery toward TAM. Interestingly, mannose targeting has also been directly applied to small molecule cathepsin inhibitors by generating glycoconjugates of monomannose, trimannose, and heptamannose with the pan-cathepsin inhibitor DCG-04 [114].…”
Section: Nanocarrier-mediated Delivery Of Cathepsin Inhibitorsmentioning
confidence: 99%
“…A key study by Holla and Skerra revealed that simple mannose-units, and especially branched oligomannosidic structures, in particular a trimannose structure (3,6-di-(α-d-mannopyranosyl)-α-d-mannopyranose) as well as fucose-containing saccharides, in particular a disaccharide (3-(β-l-fucopyranosyl)-2-acetamido-2-deoxy-β-d-glucopyranose), are recognized by DC-SIGN [25]. Based on these observations, we selected four different potential ligands for DC-SIGN that carry a poly(ethylene glycol) (PEG)-based, azide-terminated linker to enable covalent binding through azide-alkyne click reactions to nanocarriers as the target structures for total synthesis (Figure 1) A simple d-mannose monosaccharide 1 and the mentioned trimannose structure 2, which were available from earlier studies [4,26,27], as well as a fucose containing disaccharide 3 and a mannose-terminated glycodendron 4, were chosen as potential ligands. The synthesis of the fucose disaccharide 3 started from N-acetylglucosamine (5), which was deprotonated at the most acidic 1-OH position and then was β-selectively alkylated with progargyl bromide in 52% yield (Scheme 1, top) [29].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they can serve as important mediators in nanomedicine to deliver antigens upon targeting and cell uptake of antigen-loaded nanocarriers [3]. The targeting of DCs is possible through their surface receptor dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), which is known to bind carbohydrate recognition structures through a C-terminal carbohydrate recognition domain (CRD) [4][5][6]. The DC-SIGN receptor is a tetramer that carries four of these CRD domains and can therefore theoretically bind up to four ligands simultaneously [7].…”
Section: Introductionmentioning
confidence: 99%